GRAPHEN: production processes and their applications - Nascimento, José Carlos; Reis Filho, Ramílio Ramalho (Revista Interface Tecnológica, 2020)
This article is concerned with tracing a picture related to the subject of study, which can lead to a better understanding of the benefits and advantages around the studied material. It is not new that technologies have come to revolutionize the industry, and graphene is no different, with the growth of nanotechnologies, this material becomes one of the greatest discoveries, the first two-dimensional substance and with unique mechanical, thermal and mechanical mechanisms, this chemical element , became a revolutionary material that can transform current technology. This paper examines through literature searches, or chemical element graphene allotrope, an end comprising a molecular structure as properties, manufacturing processes and applications of this material.